Evaluation of Discrepancy of Parenting Class Program in order to Increase Community Satisfaction - Lutfiatul Iltiqoiyah; Hosnan Hosnan; Ahmad Walid (Al-Qalam Institute, 2023)
This study aims to evaluate the parenting program at KB-RA Al-Iman. This research is a qualitative evaluative research using the Discrepancy Evaluation Method model by Provus (1971) through 5 stages of design, installation, process, product, cost benefit analysis. Data were collected using interviews, observations and documentation studies. The sources of informants for this research are principals, teachers and parents. Based on research, the program objectives were achieved. The results of the study found that the parenting program at KB-RA Al-Iman was assessed well with a description of the design stage, installation stage, stage in schools meeting eighty percent of aspects owned by the government, stage four goals achieved so that it was of good value. In the comparison stage with other programs, each program is useful but mutually supportive. Four gaps were found in the program, namely the lack of parental involvement in the classroom, the absence of a combination of news and companion reading, caregivers participating in the program. Researchers suggest continuing this program with improvements